(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Given the widespread prevalence of moonlighting practices among employees, this research endeavours to synthesize existing research evidence with the aim of constructing a comprehensive moonlighting model that encompasses both antecedents and consequences of moonlighting behaviour. To achieve this objective, a thorough review of literature has been conducted, drawing from reputable sources such as JSTOR, Science Direct, Emerald, Springer, ACM Digital Library, ProQuest, Wiley, Sage, Web of Science, EBSCOhost, and IEEE. An examination of the gathered research evidence reveals that employees’ decisions to engage in moonlighting are influenced by factors such as financial need, exposure to opportunities, job security, financial stability management, standard of living enhancement, passion, blocked promotion, job autonomy, job satisfaction, indebtedness, financial ambition, wealth creation, and demographic profiles. The comprehensive model also incorporates the ramifications of moonlighting, encompassing aspects like mental health, physical health, socio-personal relationships, job performance, work-life balance, stress, job satisfaction, work engagement, and work commitment.